Analisis Literasi Keuangan Pada Siswa SMP Driewanti Kota Bekasi - Adhis Darussalam Pamungkas (Peneliti.net, 2022)
Financial literacy education should begin to be concentrated at school age, because the better a child's knowledge of financial literacy is, the risk of facing financial difficulties in the future can be reduced. The purpose of this study was to determine the level of financial literacy in students at Driewanti Middle School in Bekasi City. The first reason for choosing Driewanti Junior High School as the research subject was that there was information from the teachers when the economics subject learning process took place, some students still did not understand the basic concepts of financial literacy. The second reason is the disclosure of information and the granting of permission from the school. The data analysis technique used descriptive statistics. The basis of taking the total sampling. The sample collected in this study amounted to 80 people according to the total number of students and students at SMP Driewanti Bekasi City. The financial literacy indicators according to Mendari and Kewal (2013) are divided into 4 points: “a. Basic understanding and knowledge of personal finance (General Personal Finance Konowledge), b. Insights about saving and borrowing products (Saving and Borrowing), c. The basic concept of insurance and its products (Insurance), d. Includes investment and its risks (Investment)”. Chen and Volpe (1998) Measuring the level of financial literacy with 3 categories, namely: “a. If the literacy level exceeds 80 it is called high, b. Literacy level between 60 – 80, also called moderate c. Low, if the literacy level is less than 60”. The conclusions of this study are, (1) The low category is 6.25% of the total respondents. (2) A total of 58.75% of the total respondents fall into the medium category. (3) The remaining 35% is categorized as high in terms of financial literacy knowledge